1997
DOI: 10.1038/sj.ejcn.1600375
|View full text |Cite
|
Sign up to set email alerts
|

Weakness of biochemical markers of nutritional and inflammatory status as prognostic indices for growth retardation and morbidity of young children in central Africa

Abstract: Objective:To determine to what extent biochemical markers of the nutritional and in¯ammatory status of young children are related to subsequent growth retardation and morbidity. Design: Population-based follow-up study of a cohort of children from admission to ®nal survey round six months later. Setting: Health area in Northern Kivu, Zaire. Subjects: 842 children under two years of age of whom about one-third gave informed consent to capillary blood collection. Main outcome measures: Concentration of albumin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1999
1999
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Tonglet et al (22) demonstrated that subsequent height growth (over 1 to 6 mo) was lower in children with high serum concentrations of AGP, which agrees with our observations. This was illustrated by the fact that a higher proportion of children appeared to have increased serum AGP concentration (60-71%) in comparison with raised serum CRP concentrations (50-60%).…”
Section: Discussionsupporting
confidence: 93%
“…Tonglet et al (22) demonstrated that subsequent height growth (over 1 to 6 mo) was lower in children with high serum concentrations of AGP, which agrees with our observations. This was illustrated by the fact that a higher proportion of children appeared to have increased serum AGP concentration (60-71%) in comparison with raised serum CRP concentrations (50-60%).…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that serum AGP was statistically significantly related to subsequent length increment, whereas CRP almost reached significance, may be explained by this reasoning. Tonglet et al (22) demonstrated that subsequent height growth (over 1 to 6 mo) was lower in children with high serum concentrations of AGP, which agrees with our observations. The fact that in our study children with increased serum CRP concentration combined with high malaria parasite density (!5000/ mL) had lower subsequent length increment in comparison with children with normal serum CRP concentration and no malaria parasitaemia indicates that in this population malarial illness is an important determinant of linear growth retardation.…”
Section: Discussionsupporting
confidence: 93%
“…The prospective cohort study reported here was primarily designed to examine the value of anthropometric, clinical, biological, and dietary indicators in predicting short‐term morbidity of young children in rural Africa ( Tonglet 1994). Having demonstrated in a previous paper the weakness of biochemical markers of nutritional and inflammatory status as a means for risk scoring in children from the community ( Tonglet et al . 1997 ), we focus here on other possible predictors, some of which are anthropometric.…”
Section: Introductionmentioning
confidence: 99%